Functional Inhibition of Host Histone Deacetylases (HDACs) Enhances in vitro and in vivo Anti-mycobacterial Activity in Human Macrophages and in Zebrafish - Moreira, Jôsimar D.; Koch, Bjørn E. V.; van Veen, Suzanne; Walburg, Kimberley V.; Vrieling, Frank; Mara Pinto Dabés Guimarães, Tânia; Meijer, Annemarie H.; Spaink, Herman P.; Ottenhoff, Tom H. M.; Haks, Mariëlle C.; Heemskerk, Matthias T. (Frontiers in Immunology, 2020)
The rapid and persistent increase of drug-resistant Mycobacterium tuberculosis (Mtb) infections poses increasing global problems in combatting tuberculosis (TB), prompting for the development of alternative strategies including host-directed therapy (HDT). Since Mtb is an intracellular pathogen with a remarkable ability to manipulate host intracellular signaling pathways to escape from host defense, pharmacological reprogramming of the immune system represents a novel, potentially powerful therapeutic strategy that should be effective also against drug-resistant Mtb. Here, we found that host-pathogen interactions in Mtb-infected primary human macrophages affected host epigenetic features by modifying histone deacetylase (HDAC) transcriptomic levels. In addition, broad spectrum inhibition of histone deacetylases enhanced the antimicrobial response of both pro-inflammatory macrophages (Mf1) and anti-inflammatory macrophages (Mf2), while selective inhibition of class IIa HDACs mainly decreased bacterial outgrowth in Mf2. Moreover, chemical inhibition of HDAC activity during differentiation polarized macrophages into a more bactericidal phenotype with a concomitant decrease in the secretion levels of inflammatory cytokines. Importantly, in vivo chemical inhibition of HDAC activity in Mycobacterium marinum-infected zebrafish embryos, a well characterized animal model for tuberculosis, significantly reduced mycobacterial burden, validating our in vitro findings in primary human macrophages. Collectively, these data identify HDACs as druggable host targets for HDT against intracellular Mtb.